Phytosanitary state of open-field vegetable crop agroecosystems of the genus Solanum, Raphanus, Brassica in the central part of the Right-Bank Forest-Steppe of Ukraine - Shchetina, S.; Mostoviak, I.; Fedorenko , V. (Quarantine and plant protection, 2023)
Goal. Phytosanitary assessment and determination of pest and disease prevalence and development in open-field vegetable crop plantings of the genus Solanum (tomato, pepper, eggplant), genus Raphanus (radish, oilseed radish, common radish, black radish, daikon), and genus Brassica (cabbage, cauliflower, broccoli) in the Central Part of the Right-Bank Forest-Steppe Region of Ukraine. Methods. The research was conducted using established entomological, phytopathological, and horticultural methods. From 2008 to 2022, the population, distribution, and development of pests and phytopathogens were assessed in households and small farms within the Cherkasy region of Ukraine. Results. Among the dominant pest species in the agroecosystems of vegetable crops from the genus Solanum, insects accounted for 80% (8 species), followed by mites at 10% (1 species), and slugs at 10% (1 species). In agroecosystems of Brassicaceae crops, insects caused significant damage, constituting 94% (16 species) of the total pest structure, along with naked snails (1 species). The area of infestation in tomato, sweet pepper, and eggplant crops by phytophagous insects ranged from 13% to 98%, with plant damage ranging from 14% to 65%. Common spider mites accounted for 26%. Exceedances of the Economic Pest Threshold (EPT) were observed, such as Leptinotarsa decemlineata Say at 2.6 times, Gryllotalpa gryllotalpa L., Trialeurodes vaporariorum Wstw., Agrotis segetum Denis & Schiff., and Lacanobia oleracea at 2.2 times, Agriotes spp. larvae at 1.4 times, and Tetranychus urticae Koch. at 1.9 times the threshold levels. The highest area of infestation in Brassicaceae crops was found for Eurydema ventralis (46.7%), Pieris brassicae (42.4%), Agrotis segetum Denis & Schiff. (41.6%), Phyllotreta crusiferae and Phyllotreta undulate (37.6—37.8%), and Brevicoryne brassicae (26.6%). Exceedances of the EPT were recorded at 1.1—2.5 times for these pests. In the structure of the phytopathogenic complex of vegetable crop agroecosystems, fungi were dominant, accounting for an average of 49—58%. Viral pathogens had the smallest share, approximately 6—8%, causing mosaic diseases. Bacterial and oomycete agents occupied an intermediate position in the pathogenic complex structure. Nevertheless, their negative impact on plant health could be significant. Conclusions. In the Cherkasy region, which encompasses the central part of the Right-Bank Forest-Steppe of Ukraine, approximately 75% of surveyed vegetable crop plantings, including tomatoes, peppers, eggplants, radishes, oilseed radishes, common radishes, black radishes, daikons, cabbages, cauliflowers, and broccolis, exhibit high pest infestations exceeding the EPT thresholds, indicating an ecologically hazardous phytosanitary state. In these agroecosystems, insects dominated, representing 80% and 94% of the pest structure in Solanum and Brassicaceae crops, respectively. Additionally, significant damage was attributed to naked snails (Kailie gliemeži) and, in the case of Solanum crops, mites (Tetranychus urticae Koch.). EPT exceedances ranged from 1.1 to 2.5 times, depending on the pest species. Fungi, causing mycoses, dominated the phytopathogenic complex structure, ranging from 14% to 40% (max 88—90%). The prevalence of diseases varied from 21% to 38%, with disease development rates ranging from 21% to 33%. Among the identified phytopathogens, five species are among the world’s most dangerous: Pseudomonas syringae and Xanthomonas campestris (bacteria), Botrytis cinerea and Fusarium oxysporum (fungi), and Phytophthora infestans (oomycete), which require strict control of their populations.